Freshwater ecosystem services supporting humans: Pivoting from water crisis to water solutions. (September 2015) - Green, Pamela A.; Vörösmarty, Charles J.; Harrison, Ian; Farrell, Tracy; Sáenz, Leonard; Fekete, Balázs M.
Highlights: Freshwater provisioning index maps upstream water sources supporting humans downstream. 82% of global population is served by freshwater provisions exposed to high threat. Industrialized nations abate more threat to freshwater provisions than poorer nations. Sound upstream management may reduce the need for costly engineering in poorer nations. Abstract: A new global scale water indicator, the freshwater provisioning index for humans (FPIh ), maps the capacity of upstream source areas to provide water for human populations downstream. The freshwater provisioning index for humans combined with estimates of threats to water source areas assesses the compounded impacts on freshwater provisions at their point-of-service and the humans they support downstream. Nearly the entire world is serviced by freshwater sources compromised to a moderate extent through human activities, with 82% of the world's population served by upstream areas exposed to high levels of threat. Globally, 75% of the world's population benefits from engineered remediation of highly impaired source areas. Despite these gains, more than 80% of the global population still experiences moderate levels of threat impacting their freshwater provisions. Industrialized nations greatly limit their exposure to threats via infrastructure investments whereas regions in the developing world with moderate threat and little means of mitigation are viewed as the most vulnerable. Populations served by water source areas in industrialized countries receive highest threat reductions overall (50–70%) while those served by provision areas in the least developed countries receive <20% threat decrease. Better management of upstream source areas in poorer countries represents an opportunity to reduce threat lessening reliance on costly engineering solutions. Viewing the world in terms of the threats imposed on freshwater provisions combined with regional capacity to abate these impairments through infrastructure investments yields a spatial typology of freshwater resource development states reflecting region-specific challenges with unique management implications. Global mapping of threat development states provides a synoptic-scale diagnosis of key water resource challenges we link with state-specific water service management strategies including service area conservation, threat reduction, and green and gray infrastructure investments to more sustainably manage upstream freshwater provisions. This study provides a functional architecture to assess potential investment strategies to sustainably protect and manage critical upstream freshwater provisions addressing unique challenges faced by different regions of the world.